2017
DOI: 10.1371/journal.pone.0182735
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory structural assessment in craniocervical dystonia: Global and differential analyses

Abstract: IntroductionOur goal was to investigate the cortical thickness and subcortical volume in subjects with craniocervical dystonia and its subgroups.MethodsWe studied 49 subjects, 17 with cervical dystonia, 18 with blepharospasm or oromandibular dystonia, and 79 healthy controls. We performed a whole group analysis, followed by a subgroup analysis. We used Freesurfer software to measure cortical thickness, subcortical volume and to perform a primary exploratory analysis in the craniocervical dystonia group, comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…Previous conventional MRI studies have demonstrated subtle differences in the volume in multiple brain structures in patients with idiopathic dystonia. However, there is little agreement among these studies (10): Increased (12, 13) and decreased GM volume in various brain regions (1416) or even a combination of both (4648) have been observed. The discrepancies between these imaging studies seem to suggest that volume changes in idiopathic dystonia are—if present at all—rather small and, thus, difficult to detect in small cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous conventional MRI studies have demonstrated subtle differences in the volume in multiple brain structures in patients with idiopathic dystonia. However, there is little agreement among these studies (10): Increased (12, 13) and decreased GM volume in various brain regions (1416) or even a combination of both (4648) have been observed. The discrepancies between these imaging studies seem to suggest that volume changes in idiopathic dystonia are—if present at all—rather small and, thus, difficult to detect in small cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous imaging studies in idiopathic dystonia have failed so far to provide a definitive answer as to the presence and localization of morphological abnormalities (10, 11). For instance, an increased gray matter (GM) volume has been observed in the striatum and cerebral cortex in some patient cohorts (12, 13), whereas other studies have reported widespread decreases of GM volume (1416). Importantly, most previous studies are based on conventional MRI techniques showing mixed signal contrasts, which cannot be easily linked to the underlying microstructural tissue changes.…”
Section: Introductionmentioning
confidence: 99%
“…Pantano et al [3] describe a volume reduction in the putamen and caudate similar to our data, and Obermann et al [12] also describe a volume reduction in the putamen. However, there are several more recent studies reporting no volumetric difference in the BG at all [7, 13, 14]. Some studies even account of a putaminal volume increase [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…They have produced diverging, sometimes even contradicting, results. More recent reports using voxel-based morphometry (VBM) have focused on craniocervical dystonias (CCD) [7-9] and other forms of focal dystonias [10-13]. A majority of these data suggest a volume reduction in the motor, sensory, and visual cortices of the brain’s convexity [3, 10, 13, 14], while also some reports of gray matter increases in these areas exist [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation